FRI0275 ONE-YEAR TREATMENT RETENTION OF SECUKINUMAB VERSUS TUMOR NECROSIS FACTOR INHIBITORS IN SPONDYLOARTHRITIS. RESULTS FROM FIVE NORDIC BIOLOGIC REGISTRIES. (2nd June 2020) - Glintborg, B.; Lindström, U.; DI Giuseppe, D.; Aarrestad Provan, S.; Gudbjornsson, B.; Hetland, M. L.; Michelsen, B.; Wallman, J. K.; Aaltonen, K.; Hokkanen, A. M.; Schjødt Jørgensen, T.; Hansen, R. L.; et al.
Abstract : Background: Tumor necrosis factor inhibitors (TNFi) have been available for more than a decade for treatment of spondyloarthrtitis (SpA). Secukinumab (SEC) represents a new mode of action, but few studies have compared outcomes in patients(pts) treated with SEC vs TNFi – and the optimal treatment strategy in routine care remains to be established. Comparative studies between SEC and adalimumab (ADA) are ongoing. Objectives: To describe baseline characteristics and compare 1-yr treatment retention of SEC vs TNFi (ADA/certolizumab pegol(CLZ)/etanercept(ETN)/golimumab(GOL)/infliximab(IFX)) in SpA-pts from 5 Nordic countries. Methods: Observational, prospective cohort study. Pts with SpA (ankylosing spondylitis/non-radiographic axial SpA/undifferentiated SpA) starting SEC or any TNFi during 2015-2018 were identified in clinical rheumatology registries of the Nordic countries. Baseline characteristics were retrieved. Country-specific data were pooled. 1-yr treatment retention of SEC vs TNFi was assessed through crude survival probability curves, retention rates and adjusted Cox regression analyses (ADA reference). Analyses were stratified by line of bDMARD and TNFi type. Results: In total, 10692 treatment courses (834 SEC, 9858 TNFi) in 7952 patients were included. SEC was rarely used as 1 st bDMARD (Table 1 ), whereas it was the drug most frequently used as 3 rd + line (Table 2 ). Baseline characteristics were numerically similar for SEC vs TNFi (Table 1 ). 1-yr treatment retention varied between the TNFi (Figure, Table 2 ), with SEC showing retention rates comparable to ADA when used as 1 st or 2 nd line therapy. However, SEC retention was poorer than ADA when used as 3 rd + therapy, but comparable to retention of other TNFi. In adjusted Cox regression analyses, confidence intervals were wide and included 1 for SEC vs ADA (1 st, 2 nd line), whereas there was slightly poorer retention of SEC versus ADA when used as 3 rd + bDMARD (Table 2 ). Conclusion: These observational data in >10.000 biological treatment courses in SpA, showed that SEC was mainly used in bDMARD experienced pts. Baseline characteristics were similar in pts treated with SEC vs TNFi. The 1-yr retention for SEC was similar to that of the TNFi when used as 1 st or 2 nd line, but poorer than ADA regarding 3 rd + courses. Further analyses are planned to explore confounding by indication and channeling towards treatment. Acknowledgments: Glintborg/Lindström shared 1st author, Kristensten/Jacobsson shared last. Partly funded by NordForsk and FOREUM Disclosure of Interests: Bente Glintborg Grant/research support from: Grants from Pfizer, Biogen and Abbvie, Ulf Lindström: None declared, Daniela Di Giuseppe: None declared, Sella Aarrestad Provan Consultant of: Novartis, Björn Gudbjornsson Speakers bureau: Novartis and Amgen, Merete L. Hetland Grant/research support from: BMS, MSD, AbbVie, Roche, Novartis, Biogen and Pfizer, Consultant of: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck and Samsung Bioepis, Brigitte Michelsen Grant/research support from: Research support from Novartis, Consultant of: Consulting fees Novartis, Johan K Wallman Consultant of: AbbVie, Celgene, Eli Lilly, Novartis and UCB Pharma, Kalle Aaltonen: None declared, Anna-Mari Hokkanen Grant/research support from: MSD, Tanja Schjødt Jørgensen Speakers bureau: Abbvie, Pfizer, Roche, Novartis, UCB, Biogen, and Eli Lilly, Rebekka L. Hansen: None declared, Arni Jon Geirsson: None declared, Kathrine L. Grøn Grant/research support from: BMS, Niels Steen Krogh: None declared, Johan Askling Grant/research support from: JA acts or has acted as PI for agreements between Karolinska Institutet and the following entities, mainly in the context of the ARTIS national safety monitoring programme of immunomodulators in rheumatology: Abbvie, BMS, Eli Lilly, Merck, MSD, Pfizer, Roche, Samsung Bioepis, Sanofi, and UCB Pharma, Lars Erik Kristensen Consultant of: UCB Pharma (Advisory Board), Sannofi (Advisory Board), Abbvie (Advisory Board), Biogen (Advisory Board), Speakers bureau: AbbVie, Amgen, Biogen, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, Forward Pharma, Janssen Pharmaceuticals, MSD, Novartis, Pfizer, and UCB Pharma, Lennart T.H. Jacobsson Consultant of: AbbVie, Eli Lilly, Janssen, Novartis and Pfizer